Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3892/ijo_00000776
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces tumor progression and fibrosis in intrahepatic cholangiocarcinoma through an interaction with hepatic stellate cells

Abstract: Abstract. Intrahepatic cholangiocarcinoma (ICC) is characterized as a highly fatal tumor with poor prognosis because of its strong progression, early invasion, widespread metastasis and rich cancerous stroma. Although it is widely accepted that fibroblasts facilitate stromal fibrosis and tumor progression, the mechanisms of the interaction between cancer cells and activated fibroblasts have not been fully elucidated thus far. In this study, we demonstrate the presence of angiotensin II (AngII) in ICC tissues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 39 publications
1
45
1
Order By: Relevance
“…We have further suggested that circulating angiotensinogen in the blood is converted directly to Angiotensin II by trypsin in the tumor microenvironment at the weakly acidic pH found with anaerobic glycolysis [43]. We have also previously demonstrated that gastric cancer and intrahepatic cholangiocarcinoma tissue have higher levels of Angiotensin II than normal tissues [30,31]. Furthermore, gastric cancer tissue and cell lines alike have been found to express the AT1 receptor in both the current and previous studies [30,44].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We have further suggested that circulating angiotensinogen in the blood is converted directly to Angiotensin II by trypsin in the tumor microenvironment at the weakly acidic pH found with anaerobic glycolysis [43]. We have also previously demonstrated that gastric cancer and intrahepatic cholangiocarcinoma tissue have higher levels of Angiotensin II than normal tissues [30,31]. Furthermore, gastric cancer tissue and cell lines alike have been found to express the AT1 receptor in both the current and previous studies [30,44].…”
Section: Discussionmentioning
confidence: 67%
“…Previously, several studies have identified that Angiotensin II can promote cell proliferation during cancer development, and Angiotensin II type 1 (AT1) blockers (ARBs) may suppress this effect by antagonizing the AT1 receptor [30][31][32]. Furthermore, ARBs have recently attracted attention for their direct anti-fibrotic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we demonstrated that hepatic stellate cell (HSC) activation by angiotensin II (AngII) facilitated stromal fibrosis and tumor progression via an interaction with cancer cells in ICC tissues (6). Tumor progression and fibrosis are pivotal aspects of malignancy and several factors, including epidermal growth factor (EGF), transforming growth factor-β (TGF-β), hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), trypsinogen, AngII, and chemokines including SDF-1, are regarded as possibly being involved in cross-talk in tumor-stromal interactions (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…This altered stroma has been implicated in cancer development and maintenance, and also in the poor sensitivity of pancreatic cancer to chemotherapeutics. Furthermore, the interaction between carcinoma cells and stromal cells, including CAFs, influence stromal formation, invasion and metastasis (60,61).…”
Section: Effect Of Preoperative Therapy On Pancreatic Cancer Tissuesmentioning
confidence: 99%
“…Therefore, treatments that inhibit TGF-β are important in antitumor immunity (99). Metformin (100,101) and ARB (61,78,102) are well-known as drugs that inhibit TGF-β, in addition to inhibition of EMT. Although clinical effectiveness is unlikely to be achieved using one of these as an anticancer agent, it is reasonable to use these drugs for patients with comorbidities, including diabetes, hypertension and hyperlipidemia, in the treatment of pancreatic cancer.…”
Section: Effect Of Preoperative Therapy On Pancreatic Cancer Tissuesmentioning
confidence: 99%